Financial participation programs in Polish public companies - Kozłowski, Maciej (Management, 2014)
The major purpose of this article is to analyze the most important fp programs in Poland in order to increase knowledge on the subject and to show the occurring relations between the programs applied and the socioeconomic results of enterprises. The emphasis has been put on showing the multidimensional relationships between employee financial ownership and economic results, as well as on proving the relationship mechanisms of employee ownership on productivity are complex interactions by nature. Additionally, it has helped to separate crucial characteristic features of the applied forms of fp. This empirical approach concentrates on qualitative research and not quantitative, which although broad based, does not precisely identify the aforementioned relationships too precisely.
Keywords: financiranje; javna podjetja; javno-zasebno partnerstvo; lastništvo; Poland; Poljska; poslovna uspešnost; produktivnost; zaposleni